Investigation of line displacement in terms of electrical field distribution and safe right of way distance in energy transmission systems - Kumru, Celal Fadil; Arikan, Oktay (PAMUKKALE UNIV, 2020)
One of the important topics to be examined in the energy transmission lines is the effects of the electric field generated by the lines on the public areas around it. It is essential to leave enough spaces between the transmission lines and the living areas in order to prevent the risks of potential discharges and the electric field caused by high voltage. Today, due to the rapidly growing population and expanding residential areas, the situations where overhead transmission lines pass through or get close to living spaces can be encountered. Therefore, it is very important to calculate and measure the electrical field values caused by the transmission lines in the living areas and to determine the critical safe right of way distances in terms of human health. In this study, electric field analysis are performed by taking into account two lines, double circuit 154 kV and single circuit 400 kV, for separate routes and displaced on single tower. Modeling study is performed by Comsol Multiphysics software based on finite element method. By the help of the results obtained, safe right of way distances are determined in accordance with international criteria.
Keywords: Electric field analysis; Energy transmission lines; Finite element method; Engineering